Microbial respiration, ATP and biomass in soils of Swartboskloof, Jonkershoek, under mountain fynbos subjected to a prescribed burn - Van Reenen, Carol A.(Carol Ann) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.